Antagonisms in the Phillips Curves with a positive slope: Mexico and Spain’s case - Rubén E. Roa Dueñas (Estudios Fronterizos, 2002)
This document presents the indispensable theoretical aspects of the Phillips curve, as well as its evolution. A brief relation of the causes and effects of the Mexican 1994 crisis, as well as the consequent and visible noncompliance of the Phillips input. In same way we present the inclusion of Spain to the European Economic Community through the consummation of the Maastricht Treaty, its environment and some of its consequences, whose economy usually shows a vigorous and prosperous character. We conclude that the so-called inverted relation between unemployment and inflation which grossly shows the Phillips curve and the situations that do not comply with that norm, take us to a debate about the scenery and the required tools used by the different economies to try to defeat this theory, tending to direct the curve to the beginning, such as the Spain case. We can mention that it is not that important to defeat it in theory, but to generate the required conditions to consolidate the economy, as a future platform of sustained social and economical development.